FIRST RECORD OF OCTOCHAETID EARTHWORMS FROM A SELECTED REGION OF THE GANGETIC PLAIN OF BIHAR, INDIA - ROHIT SRIVASTAVA; MRIDULA KUMARI; DEOKANT; SAMIR KUMAR MANDAL; SHEELU KACHHAP; SHALINI; SWETA SUBARNA; NEHA SWATI BAXLA; MANOJ KUMAR; SUKUMAR DANDAPAT; et al. (The Bioscan, 2021)
The paper deals with the earthworm diversity belonging to the family Octochaetidae form selected area of the Gangetic plain of Bihar. This is the first record of earthworms from this region as no previous systematic report in the earthworm biodiversity is available till date. Five Octochaetide species were found during the study belonging to four genera Octochaetona, Dichogaster, Lennogaster and Eutyphoeus. The five species recorded are Octochaetona surensis Michaelsen, Dichogaster affinis Michaelsen, Dichogaster bolaui Michaelsen, Lennogaster pusillus Stephenson Eutyphoeus waltoni Michaelsen. The two species namely Dichogaster affinis and Dichogaster bolaui are peregrine and epigeic while Lennogaster pusillus is native and epigeic. Rest two species Octochaetona surensis and Eutyphoeus waltoni are native and endogeic species.